Distribution of phlebotomine sand flies (Diptera: Psychodidae) in limestone caves, Khao Pathawi, Uthai Thani province, Thailand - R. Polseela (2018)
© 2015, SEAMEO TROPMED Network. All rights reserved. This study investigated the species composition and density of the sand flies found inside four limestone caves at Khao Pathawi, Thap Than District, Uthai Thani Province. Sand flies were collected using Centers for Disease Control (CDC) light traps from October 2012 to September 2013. The sand flies were captured between 06:00 pm - 06:00 am. A total of 11,817 sand flies were collected with a male:female ratio of 1.0:1.2 (5,325:6,492). The specimens were identified as eight species belonging to three genera Phlebotomus, Sergentomyia, Chinius, and comprised of S. anodontis, P. argentipes, P. stantoni, S. barraudi, S. silvatica, S. gemmea, S. indica, and C. barbazani. Sergentomyia anodontis (55.0%) was the predominant species followed by P. argentipes (33.6%) and others. Five species of sand fly were found throughout the year in this area: P. argentipes, P. stantoni, S. anodontis, S. barraudi and S. gemmea. The highest average density of sand flies was found in Ratree cave (35.0 sand flies per trap per night) and lowest in Bandai cave (29.0 sand flies per trap per night). The population of sand fly fluctuated from the highest peak in December (28.5%) to the lowest peak in May (2.3%). The distribution of sand fly species in attraction areas is important for the control program of infection risk of leishmaniasis.